Dietas funcionais para peixes de aquacultura - Pinto, Olívia Patrícia Gonçalves (2020)
This study aimed to test the effects on growth performance, body composition and feed conversion of European seabass Bass (Dicentrarchus labrax) fed a blend of macro and microalgae. For this purpose, 4 isoproteic experimental diets (50.0% on a dry basis), isolipidic (16.2% dry base) and isoenergetic (20.9 KJ/g dry basis) diets were produced with different inclusion rates (0%, 2%, 4% and 6%) of a mixture of 2 microalgae (Chlorella sp. and Nannochloropsis sp.) and two macroalgae (Gracilaria sp. and Ulva sp.). To evaluate the effects of the diets, a growth trial was carried out in triplicate groups of fish with an average ad weight and length of 11.3 ± 2.7 g and 10.5 ± 1.0 cm, respectively, distributed by 12 tanks (46 fish per tank). Fish were fed three times a day by automatic feeders until apparent satiety. The conditions of temperature, pH and salinity of the water were controlled daily in order to meets species needs. Obtained results showed that the blend inclusion in the diets caused a significant increase (P<0.05) in the weight and final length of the fish, and the highest value was presented by the fish that were fed the diet with 6% inclusion rate (62.9 g and 17.7 cm, respectively). There was also a significant increase in the condition factor, voluntary feed intake, specific growth rate and protein efficiency ratio in fish fed Algae 6%. The highest FCR was registered in fish fed the control diet (1,35 ± 0,06) and the lowest in the ones fed with 4% of algae supplementation (1.22 ± 0.011). A significant increase (P<0.001) of hepatosomatic index was observed from a value of 0.953 corresponding to the control up to 1.42 for the diet with 6% supplementation. There were no significant differences (P≥0.126) in whole body ash and protein content, but lipids and body energy showed a significant increase (P<0.001) in fish fed the algal blend. The algae blend caused a significantly higher (P≤0.002) gain of dry matter, lipids, protein and energy when compared to the control diet (0% inclusion). There was a significant increase (P<0.05) in all retention parameters (dry matter, lipids and energy) except for protein retention that did not present significant variations among diets. In conclusion, it is perceptible that algae supplementation proved to bring beneficial effects for European seabass in terms of growth, feed intake, feed conversion rate and nutrient retention. However, it was also notorious that 6% inclusion rate caused a greater body fat gain which may lead to organoleptic changes, so in the future it would be advisable to use inclusion levels below 6%.